PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH MERGER DAN AKUISISI (PADA PERUSAHAAN PENGAKUISISI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2004-2006) - Hamidah, Hamidah; Noviani, Manasye (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2013)
The purpose of this study was to examine the differences in the financial performance of the acquirer pre and post mergers and acquisitions. Financial performance is measured with some ratios, Current Ratio (CR), Total Assets Turnover (TATO), Debt Ratio (DR), Return on Assets (ROA), and Price Earnings Ratio (PER). Population of this study included all public company which conducted merger and acquisition(M & A) activity in the period 2004-2006. The samples were 10 companies that were taken by purposive sampling method. Analysis of the data used to test hypotheses using Paired Sample t-Test. Empirical results shows that there are no significant difference for DR and TATO in testing 1 year before and 1 year after M & A up to 1 year before and 5 years after M & A. However, CR shows significant difference in test 1 year before with 2, 4, and 5 years after M & A; ROA shows significant difference in test 1 year before with 4 years after M & A; then PER shows significant difference in test 1 year before with 3 years after M & A. Key words: Financial Performance, Merger, Acquisition.